2020
DOI: 10.1016/j.jbusres.2018.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Territorial brand management: Beer, authenticity, and sense of place

Abstract: This paper explores brand management decisions concerning the terroir product of an authentic beer brand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 49 publications
0
24
0
1
Order By: Relevance
“…Neolocalism, "a conscious effort by businesses to foster a sense of place based on attributes of their community" (Holtkamp et al 2016, p. 66), has received substantial and prolonged attention in the context of microbreweries and craft beer (e.g., Flack 1997;Schnell and Reese 2003;Garavaglia 2020) since the introduction of the concept by Shortridge (1996). While the early studies focused on identifying the most obvious expressions of neolocalism in beer names and labels, their significance to the marketing of craft beer and brand management has lately attracted growing attention (e.g., Sjölander-Lindqvist et al 2019;Melewar and Skinner 2020). These studies have confirmed the notion that local ties are cultivated intentionally rather than by necessity (Zelinsky 2011), and not only constructed, as they also need to be maintained actively (Schnell andReese 2003, 2014;Schnell 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Neolocalism, "a conscious effort by businesses to foster a sense of place based on attributes of their community" (Holtkamp et al 2016, p. 66), has received substantial and prolonged attention in the context of microbreweries and craft beer (e.g., Flack 1997;Schnell and Reese 2003;Garavaglia 2020) since the introduction of the concept by Shortridge (1996). While the early studies focused on identifying the most obvious expressions of neolocalism in beer names and labels, their significance to the marketing of craft beer and brand management has lately attracted growing attention (e.g., Sjölander-Lindqvist et al 2019;Melewar and Skinner 2020). These studies have confirmed the notion that local ties are cultivated intentionally rather than by necessity (Zelinsky 2011), and not only constructed, as they also need to be maintained actively (Schnell andReese 2003, 2014;Schnell 2013).…”
Section: Introductionmentioning
confidence: 99%
“…At this level, we found that in some industries, firms’ family nature represented the expression of local cultures and was also interpreted as a territorial developing force by local communities (Liu & Gao, 2014; Tessari & Godley, 2014). In this vein, Melewar and Skinner (2018) demonstrated that for consumers, firms’ family nature is a prototypical feature of local industrial organizations. Specifically, they found that for consumers, family ownership was a signal of quality and authenticity as well as a structuring force that helped to make brewing an area-salient industrial activity.…”
Section: Resultsmentioning
confidence: 99%
“…First, consumers are more likely to consider small and family-owned businesses as more authentic than large-scale and chain-affiliated ones (Kovács et al, 2013). Second, a product’s link to a place of origin where it is grown, prepared, or manufactured, which is the main attribute along which consumers evaluate market offerings’ authenticity (Beverland, 2006; Grayson & Martinec, 2004), has been found to be amplified when connected to a family firm (Lude & Prügl, 2018; Melewar & Skinner, 2018). Third, scholars have also found that a firm’s fidelity to its history and the continuity of how it behaves in the marketplace are potent sources of perceived authenticity (Beverland, 2006; Morhart, Malär, Guèvremont, Girardin, & Grohmann, 2015).…”
Section: Firms’ Family Nature and A Future Research Agendamentioning
confidence: 99%
“…Gastronomic, or culinary tourism, has been receiving a lot of recent attention in the literature, as this form of tourism is seen to contribute to deep, meaningful, and memorable tourism experiences (Li, et al, 2018). Yet much of the extant literature considers these issues from the demand side of the consumer rather than considering the managerial decisions of the supplier (Kline, Greenwood and Joyner, 2015;Melewar and Skinner, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Within this body of literature much has also been written about authenticity. When related to food and drink, this can include authenticity claims about the Country of Origin (COO) of gastronomic products (Melewar and Skinner 2018), how food and drink is produced, or how it connects the consumer with the producer and the culture, heritage and traditions of a place and the tourism experiences that it offers (Kline, Greenwood and Joyner, 2015). Even though there is a well-established and broad body of literature on COO, gaps do remain that this paper will attempt to fill as part of its contribution to knowledge.…”
Section: Introductionmentioning
confidence: 99%